PENINGKATAN AKTIVITAS DAN HASIL BELAJAR QUR’AN HADITS MELALUI BELAJAR KELOMPOK - Musryid, Adhar Al (STIT Pringsewu, 2017)
AbstractFactor motivate in studying believed very have influencing acquirement of achievement learn student. Ironically more than 60 % student do not have activity for studying of Quran Hadits, so that require to be research of class action with aim to.; (1) Depicting the make-up of student activity in studying team-work.(2) Depicting the make-up of result learn student in studying team-work. Research of this Class Action is in 3 ( three ) Rotation, in each its cycle consist of phases: planning, action, perception/ data collecting and of refleksi. To obtain get student activity data of user observer team kolabolator, and data result of learning to be obtained to tes written. Result of action indicate that team-work can improve result and activity learn student in studying of MA Darul Ulum Result of action at student activity equal to to 92.50 ( Cycle one), 92.92 ( Cycle two), and 93.55 ( Cycle three), and result learn student 66,77 (Cycle one), 68,40 ( Cycle two), and 70,70 ( Cycle three).